ADVOKASI LSM SOSIAL MEDIA SOCIAL MOVEMENT INSTITUE TERHADAP HEGEMONI PEMERINTAH DALAM SENSOR MEDIA DAN KEBEBASAN BERPENDAPAT DI RUANG DIGITAL - Dio Alfianto Esha Mahendra; Hanantyo Sri Nugroho (Program Studi Ilmu Pemerintahan FISIP Universitas Galuh, 2025)
The development of digital technology has encouraged public awareness to utilize various digital media platforms to obtain information and exchange ideas, as an effort to protect and secure the Indonesian people from various threats in the digital world, the government issued a policy regarding the Implementation of a private electronic system that allows the government to gain access to take down content that is considered to violate laws and regulations, indicating the government's efforts to build hegemony and control over civil society as a subordinate group. In this study, an analysis was conducted to determine how the policy of Implementing a private electronic system through content censorship on social media can build government hegemony as well as the impact of content censorship on freedom of expression in the digital space such as the emergence of anti-hegemony groups to the emergence of pressure groups. This study uses a qualitative research method with a case study approach so that researchers can obtain a deeper picture of the phenomenon being studied. This study emphasizes the conditions of the Social Movement Institute group after the implementation of a policy that allows the government to control content on social media